Pain extent is associated with Central Sensitization Inventory but not widespread pressure pain sensitivity or psychological variables in women with fibromyalgia. (4th May 2023) - Cigarán-Méndez, M; Úbeda-D'Ocasar, E; Arias-Buría, JL; Fernández-de-Las-Peñas, C; Barbero, M; Gallego-Sendarrubias, GM; Valera-Calero, JA
Abstract : Objective: To investigate the relationship between pain extent, as a clinical sign of central sensitization, and clinical, psychological, and pressure sensitivity in women with fibromyalgia syndrome (FMS). Method: In this study, 126 females with FMS completed demographic (age, gender, body mass index, height, weight), clinical (pain history, and pain intensity at rest and during daily living activities), psychological (depression and anxiety levels), and neurophysiological [pressure pain threshold (PPT)] assessments. The Central Sensitization Inventory (CSI) was also used to collect self-reported symptoms of sensitization. Pain extent and frequency maps were obtained from pain drawings using customized software. After conducting a multivariable correlation analysis to determine the relationships between variables, a stepwise linear regression model analysis was performed to identify variables associated with pain extent. Results: Pain extent was positively associated with age (r = 0.17), years with pain (r = 0.27), pain during daily life activities (r = 0.27), and CSI (r = 0.42) (all p < 0.05). The stepwise regression analysis revealed that 27.8% of the pain extent was explained by CSI, age, and years with pain. Conclusions: This study found that larger pain extent was associated with self-reported outcomes, i.e. CSI, but not neurophysiological outcomes, i.e. PPTs, of sensitization in women with FMS. Older age and a longer history with pain symptoms were also associated with larger pain extent.